(untitled) (African Journal of Biomedical Research, 2022)
Lactic acid bacteria (LAB) are naturally found as part of fermented food products and other foodstuff. These organisms are used in the fermentation of vegetables to improve their nutritional value, acceptability, palatability, as well as microbiological quality and shelf life. Standard microbiological techniques were used to examine 85 different food products for the presence of LAB. The crowded plate approach was used to screen distinct isolates for bacteriocin producing capacity. PCR-based techniques (16S rRNA) were used to identify and characterize lactic acid bacteria associated with food products that have the potential to produce bacteriocins. A total of five hundred and sixty-one (561) lactic acid bacteria were isolated from the food samples of which only 8 (1.42 %) were positive for bacteriocin production. The best five isolates from the 14 with an inhibition zone of 20 mm and more were identified as Lactobacillus plantarum strain PMM09-2528L, Lactobacillus acidophilus strain NK-S10, Lactococcus lactis subsp. lactis strain IFM 63517, Leuconostoc mesenteroides strain M6 and Pediococcus cellicola strain PMM-25. These bacteriocinogenic LAB can be used in the formulation of starter cultures and for commercial use in the biopreservation of vegetables and other food products